Specifically formulated ketogenic, low carbohydrate, and carnivore diets can prevent migraine: a perspective - Stanton, Angela A. (Frontiers in Nutrition, 2024)
This article presents a hypothesis explaining the cause of migraines, suggesting that electrolyte imbalance, specifically a lack of sufficient sodium in the extracellular space of sensory neurons, leads to failed action potentials. The author argues that migraines are triggered when sodium channels fail to initiate action potentials, preventing communication between neurons. The article discusses the evolutionary perspective of the migraine brain, stating that migraineurs have a hypersensitive brain with more sensory neuronal connections, making them more reactive to environmental stimuli and in need of more minerals for the increased sensory neuronal communication. Since glucose is often used to reduce serum hypernatremia, it follows that a high carbohydrate diet reduces sodium availability for use in the brain, causing an electrolyte imbalance. Low carbohydrate diets, such as ketogenic, low carb-high fat (LCHF), and carnivore (all animal products), can be beneficial for migraineurs by reducing/eliminating carbohydrate intake, thereby increasing sodium availability. In support, many research papers and some anecdotal evidences are referred to. The article concludes by proposing lifestyle modifications, such as dietary changes and sodium intake management. These will provide migraineurs with a long-term healthy metabolic foundation helping them to maintain strong nutritional adherence and with that aiding continued proper neuronal functioning and migraine free life.